2017
DOI: 10.1016/j.semcdb.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB3 and B4: From biochemistry to biology

Abstract: Human SERPINB3 and SERPINB4 are evolutionary duplicated serine/cysteine protease inhibitors. Genomic analysis indicates that these paralogous genes were encoded from independent loci arising from tandem gene duplication. Although the two molecules share 92% identity of their amino acid sequences, they are distinct in the Reactive Center Loop (RCL) including a hinge region and catalytic sequences which accounts for altered substrate specificity. Elevated expression of the two molecules have been reported to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 106 publications
1
85
0
Order By: Relevance
“…SERPINB3 (formerly known as squamous cell carcinoma antigen-1) is a Clade B Serine Protease Inhibitor physiologically found in the spinous and granular layers of normal squamous epithelium, such as tongue, lungs, uterus and others, while become overexpressed by neoplastic cells of these organs [40] . Recent studies showed that an aberrant expression of this protein also extends to cancers of other origin such as HCC [41] .…”
Section: Serpinb3mentioning
confidence: 99%
“…SERPINB3 (formerly known as squamous cell carcinoma antigen-1) is a Clade B Serine Protease Inhibitor physiologically found in the spinous and granular layers of normal squamous epithelium, such as tongue, lungs, uterus and others, while become overexpressed by neoplastic cells of these organs [40] . Recent studies showed that an aberrant expression of this protein also extends to cancers of other origin such as HCC [41] .…”
Section: Serpinb3mentioning
confidence: 99%
“…More recently, the role of SCCA1‐1 has been reported in inhibiting reactive oxygen species generation and cell death through its inhibitory interaction with respiratory complex I . In addition, these and other studies have highlighted a significant association between SCCA1‐1 overexpression and poor prognosis, also associated with chemoresistance in different tumor types …”
Section: Introductionmentioning
confidence: 86%
“…Squamous cell carcinoma antigen‐1 is a serine protease inhibitor that belongs to the clade B subset of serpins and includes the 2 isoforms SCCA1‐1 (also known as SerpinB3) and SCCA1‐2 (also known as SerpinB4) . The first described isoform, SCCA1‐1, was initially found to be significantly overexpressed in carcinomas with squamous differentiation, but recent evidence also extends to adenocarcinoma of the lung, breast, and pancreas, as well as hepatocellular carcinoma . The SCCA1‐1 isoform confers to cancer cells resistance to induced apoptosis by different mechanisms, including inhibition of lysosomal cathepsin proteases, the JNK pathway, or p38 activation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations